2006
DOI: 10.1016/j.yjmcc.2005.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia/reperfusion-induced death of cardiac myocytes: possible involvement of nitric oxide in the coordination of ATP supply and demand during ischemia

Abstract: Nitric oxide (NO) has been known to play various functional and pathological roles as an intracellular or intercellular messenger in the heart. In this study, we investigated whether NO produced during ischemia was involved in the coordination of ATP supply and demand, and also in protection from cell death using cultured cardiac myocytes. Unexpectedly, the survival rate of myocytes for 3 h simulated ischemia (SI) was increased as compared with that for 2 h SI at 24 h after reperfusion. The cellular ATP level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…In this study, the extracellular ATP-purinoceptor system was possibly involved in cardiomyocytes [11]. In addition, Feron et al [26] have revealed that eNOS is found in caveolin-3-containing lipid rafts in cardiomyocytes, and that elevations in intracellular Ca 2+ cause the activation of eNOS, further supporting our inference that NO was involved in the suppression of ATP release via Cx43 hemichannels.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…In this study, the extracellular ATP-purinoceptor system was possibly involved in cardiomyocytes [11]. In addition, Feron et al [26] have revealed that eNOS is found in caveolin-3-containing lipid rafts in cardiomyocytes, and that elevations in intracellular Ca 2+ cause the activation of eNOS, further supporting our inference that NO was involved in the suppression of ATP release via Cx43 hemichannels.…”
Section: Discussionsupporting
confidence: 85%
“…We first investigated the underlining mechanisms for this transient ATP increase caused by the exposure to OGD. The concentration of intracellular ATP did not decrease, but rather increased probably due to a reduction in ATP utilization, since spontaneous and rhythmic contractions were almost completely abolished at 1 h and 2 h after the onset of OGD [11]. However, the intracellular ATP was markedly decreased at 3 h OGD due to continued suppression of the production of ATP.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations